2023
DOI: 10.1097/01.hjh.0000939388.26095.12
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of the Wall to Lumen Ratio of Retinal Arterioles Evaluated by Adaptive Optics in Human Hypertension

Abstract: Objective: Structural alterations in the microcirculation may be considered an important mechanism of hypertension-mediated organ damage. An increased media to lumen ratio of subcutaneous small resistance arteries evaluated with locally invasive techniques (biopsies of subcutaneous fat, micromyography) may predict the subsequent development of cardiovascular events. However, it is not presently known whether structural alterations of retinal arterioles evaluated with a non-invasive approach (adapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The evidence was confirmed after restricting the analysis to cardiovascular events, excluding deaths and neoplastic diseases [82]. Therefore, the structural alterations of retinal arterioles evaluated by adaptive optics may predict total and cardiovascular events [82].…”
Section: Prognostic Role Of Microvascular Structural Alterationsmentioning
confidence: 81%
See 2 more Smart Citations
“…The evidence was confirmed after restricting the analysis to cardiovascular events, excluding deaths and neoplastic diseases [82]. Therefore, the structural alterations of retinal arterioles evaluated by adaptive optics may predict total and cardiovascular events [82].…”
Section: Prognostic Role Of Microvascular Structural Alterationsmentioning
confidence: 81%
“…Most recently, the prognostic role of WLR evaluated with adaptive optics was demonstrated [80]. The event-free survival was significantly worse in 230 normotensive subjects and hypertensive patients with a baseline WLR higher than the median value of the population (0.28) according to Kaplan-Meier survival curves and multivariate analysis (Cox's proportional hazard model) [82]. The evidence was confirmed after restricting the analysis to cardiovascular events, excluding deaths and neoplastic diseases [82].…”
Section: Prognostic Role Of Microvascular Structural Alterationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Only SLDF and AO can estimate the wall thickness-tointernal diameter ratio (wall/lumen ratio, WLR) of retinal arterioles, and they are used in the analysis of microvascular changes in cardiometabolic diseases, such as hypertension, diabetes, and obesity, and to predict the risk of cerebrovascular events [2,6,10,11]. AO provides a more accurate and precise estimation of the WLR of retinal arterioles compared to SLDF and allows for differentiation between functional narrowing (due to autoregulation) and structural remodelling of a vessel [6,11]. Multiple studies reported a strong relationship between retinal vessel calibre in hypertension and diabetes mellitus [2,6,7,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…AO provides a more accurate and precise estimation of the WLR of retinal arterioles compared to SLDF and allows for differentiation between functional narrowing (due to autoregulation) and structural remodelling of a vessel [6,11]. Multiple studies reported a strong relationship between retinal vessel calibre in hypertension and diabetes mellitus [2,6,7,[10][11][12]. In these two primary systemic diseases, micro-and macrovascular changes occur in longterm observation, and narrowing of retinal arterioles is a commonly described sign of retinopathy [2,6,[11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%